The constitution of law : legality in a time of emergency - Dyzenhaus, David (Cambridge : Cambridge University Press, 2006)
Deals with the urgent question of how governments should respond to emergencies and terrorism by exploring the idea that there is an unwritten constitution of law, exemplified in the common law constitution of Commonwealth countries.
Legality in a time of emergency -- Constituting the legislature -- Taking the administrative state seriously -- Unity of public law.
Includes bibliographical references (pages 234-241) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: War and emergency legislation; Mesures d'exception.; LAW -- Administrative Law & Regulatory Practice; War and emergency legislation; Electronic book